الضوابط الشرعية للقرض و آثارها في الاقتصاد الاسلامي - امال, خالدي (University of Eloued جامعة الوادي, 2017)
تناولت هذه المذكرة موضوع : الضوابط الشرعية للقرض وآثارها في الاقتصاد الإسلامي، وكان يتمحور حول الإشكال الرئيس الذي تسعى للإجابة عليه: ما هي الضوابط الشرعية للقرض وآثارها في الاقتصاد الإسلامي؟ ولقد حاولت من خلال هذه الدراسة الإجابة بالقدر الممكن على ذلك من خلال المباحث التالية : المبحث الأول أفردته لمفهوم القرض وأدلة مشروعيته وحكمه في الاقتصاد الإسلامي، أما المبحث الثاني يتضمن أركان وشروط القرض وتوثيقه، والمبحث الثالث ذكرت فيه آداب التعامل بين المقترض والمقرض، وأما المبحث الرابع فَخَصصته لأنواع القروض وآثارها في الاقتصاد الإسلامي ، وفي الأخير الخاتمة التي اشتملت على أهم النتائج والتوصيات. This note dealt with the subject of Shari'a controls on the loan and its effects on the Islamic economy. It focused on the main problem that it seeks to answer: What are the legitimate controls of the loan and its effects on the Islamic economy? I have tried through this study to answer as much as possible through the following investigations: The first section devoted to the concept of the loan and evidence of legitimacy and ruling in the Islamic economy, the second section includes the terms and conditions of the loan and documentation, and the third section mentioned the ethics of dealing between the borrower and the lender, For the types of loans and their effects in the Islamic economy, and finally the conclusion, which included the most important findings and recommendations.
مذكرة ماستر تخصص معاملات مالية
Keywords: القرض الحسن، القرض الإسلامي; Al Qarad Al Hassan, Islamic Loan